2008
DOI: 10.18553/jmcp.2008.14.9.870
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Use of Pharmaceuticals Among Patients With Irritable Bowel Syndrome in Primary Care

Abstract: BACKGROUND: Irritable bowel syndrome (IBS) has an estimated 10%-12% prevalence in industrial countries. Studies from the United States have shown that IBS causes notable financial losses for employers. Due to the lack of pathophysiological markers, only a fraction of the pharmacological management of IBS has focused on etiological mechanisms. We hypothesized that there is a high consumption of nonspecific drugs among patients with IBS in their attempts to manage symptoms.OBJECTIVE: To analyze self-reported use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
11
1
Order By: Relevance
“…fasting or (meal) stimulated condition, expression and activity of SERT, reuptake of serotonin within the gut and transport of serotonin in liver, lungs and platelets and presence of concurrent psychopathology in IBS patients such as anxiety and depression . Interpretation of published data on human serotonin metabolism in IBS is further hampered by factors such as sample processing, the analytical technique used, small sample size studies, the heterogeneous nature of IBS, imbalance in distribution among IBS subtypes, sampling in fasting vs. post‐prandial state, presence of psychopathology and use of drugs prescribed for IBS that modify GI function or the 5‐HT system . Large studies are needed, preferably from well‐characterised IBS patient groups that assess parameters of 5‐HT metabolism taking into account IBS subtypes and potential confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…fasting or (meal) stimulated condition, expression and activity of SERT, reuptake of serotonin within the gut and transport of serotonin in liver, lungs and platelets and presence of concurrent psychopathology in IBS patients such as anxiety and depression . Interpretation of published data on human serotonin metabolism in IBS is further hampered by factors such as sample processing, the analytical technique used, small sample size studies, the heterogeneous nature of IBS, imbalance in distribution among IBS subtypes, sampling in fasting vs. post‐prandial state, presence of psychopathology and use of drugs prescribed for IBS that modify GI function or the 5‐HT system . Large studies are needed, preferably from well‐characterised IBS patient groups that assess parameters of 5‐HT metabolism taking into account IBS subtypes and potential confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…17 A similar study on 374 patients in Sweden showed that acid-suppressive agents were the most commonly used drugs for abdominal complaints by IBS patients, for nonabdominal complaints, 13.3% of IBS patients selfmedicated with antidepressants. 18 According to a previous study, antacids were regularly prescribed during the high-dose steroid therapy to prevent gastritis, and in this context, oxethazaine-antacid is expected to provide greater pain relief and control of symptoms in gastritis. Given the fact that IBS has broad range of physiological and psychological alterations, the optimal treatment strategy for its management has yet to be identified.…”
Section: Indications Of Anaesthetic Antacidsmentioning
confidence: 99%
“…Patients with IBS have higher levels of depression, anxiety, and somatoform disorders than healthy persons or patients with organic disease 8 . The use of antidepressants in patients with IBS is three times higher than in controls in the general population 9 . Tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) are commonly used to treat IBS.…”
Section: Introductionmentioning
confidence: 99%
“…8 The use of antidepressants in patients with IBS is three times higher than in controls in the general population. 9 Tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) are commonly used to treat IBS. While SSRIs are used in IBS-C because of their prokinetic effect, TCAs are effective in IBS-D because they prolong whole-gut transit times.…”
Section: Introductionmentioning
confidence: 99%